TALABALARǴA NEMEC TILIN ÚYRETIWDE ERTEKLERDIŃ TÁRBIYALÍQ ORNÍ - Esbergenova, Gumshagul Bekbergenovna (SCIENCE and SOCIETY, 2026)
This article primarily focuses on the importance of fairy tales in learning German and their educational role. Fairy tales help children reflect diligence, honesty, wisdom, justice, and human qualities.